A Broadband Plasmonic Metasurface Superabsorber at Optical Frequencies: Analytical Design Framework and Demonstration. Issue 16 (10th June 2018) - Nagarajan, Arvind; Vivek, Kumar; Shah, Manav; Achanta, Venu Gopal; Gerini, Giampiero
Abstract: Plasmonic metasurface based superabsorbers exhibit high absorbance. While the absorption peak can be tuned by the geometry/size of the sub‐wavelength resonator, broadband absorption can be obtained by harnessing spectrally shifted resonances of multiple resonators of various size/shapes in a unit cell. Metal dispersion hinders high‐performance broadband absorption at optical frequencies and careful designing is essential to achieve good structures. A novel analytical framework is proposed for designing a broadband superabsorber which is much faster than the time consuming full‐wave simulations that are employed so far. Analytical expressions are derived for the wavelength dependency of the design parameters, which are then used in the optimization of broadband absorption. Numerical simulations report an average polarization‐independent absorption of ≈97% in the 450–950 nm spectral region with a near unity absorption (99.36%) in the 500–850 nm region. Experimentally, an average absorption over 98% is demonstrated in the 450–950 nm spectral region at 20° incident angle. The designed superabsorber is polarization insensitive and has a weak launch angle dependency. The proposed framework simplifies the design process and provides a quicker optimal solution for high‐performance broadband superabsorbers. Abstract : A novel analytical framework to design a broadband plasmonic metasurface superabsorber at optical frequencies is presented. A broadband near‐unity absorption is demonstrated both numerically and experimentally. The presented framework is suitable for an efficient and fully analytical design of metasurfaces. The fabricated superabsorber structure shows excellent response over broad incidence angles and polarizations.